Pembuatan Alat Komposter Dalam Pemaksimalan SDGs Desa Peduli Lingkungan Darat dan Mengatasi Permasalahan Sanitasi Lingkungan di Desa Kencong - Wonnink, Riqbal Fauzi Salman; Arsita, Selly; Setiawan, Ardhi Harry; Dini, Widya Septian; Hidayah, Siti; Triningsih, Jessica Septina; Hakim, M. Arief Rahman; Qibtiyah, Mariyatul; Imamah, Alfia Nur; Pramesty, Intan Budi; Agustin, Almaidah Sela; Aulia, Dita; Andriana, Fany Septi; Dwiguna, Ratnanda Kresna; Hidayat, Moh. Masyrofi; Yasin, Mohammad Zeqi (Peneliti.net, 2024)
The KKN-Collaborative Group #2 004 Kencong Village has a focus on maximizing the village's SDGs on the points of Village Care for the Land Environment and Village Consumption Production Villages that are Environmentally Aware. This is because the KKN 004 Kencong Village group sees the potential for processing wet and organic waste which can be utilized to become zero waste with the theme of environmental sanitation. In line with this goal, we found that there was a scarcity of fertilizer availability and a significant increase in the price of chemical fertilizers, without any reduction in demand. from farmers who do not decrease and tend to increase. It is necessary to make alternative fertilizers that can be made at home, namely by using a composter. This research was conducted using the PAR (Participatory Action Research) method. PAR is a method of raising public awareness about existing potentials and problems and encouraging community participation or participation in change activities that will be implemented. The implementation stage of the composter work program activities begins with the procurement of materials and tools as well as the assembly of composter tools which are carried out at KKN posts, then socialization and training are carried out aimed at the Kencong Village community, especially village officials, PKK, Posyandu Cadres, and farmers. The presence of the KKN-K 004 student work program in Kencong Village provided ideas and encouraged the community in terms of managing organic waste as well as household waste. So that it is hoped that the Kencong Village community will be able to become a sustainable society.